Identifying the Subjects in Which Sixth-Grade Students Have Difficulty Learning in Science Lessons, as well as the Causes of the Problems and Possible Solutions - Emre Yıldız; Ümit Şimşek (Anı Publishing, 2022)
This researched aimed to determine the subjects that 6th grade students have learning problems, the reasons for the problems and the suggestions for the solution of the problems. Cross-sectional scanning model has been adopted in the study. In the research, in the 2016-2017 academic year, 1959 6th grade students in Erzurum and 141 science teachers who teach at this grade level were studied. The data were collected through the Learning Problems Identification Questionnaire and the Teacher Learning Problems Identification Survey. Descriptive statistics and content analysis were used in analyzing the data. It was determined that the students experienced the problems in Curriculum System and Force and Motion subjects, learning difficulties, low motivation, increased anxiety and non-persistent knowledge. This situation arises from the reasons that the subject is difficult, orienting to memorization, confusing the concepts, the lesson / subject is boring, they are stressful, they are not given the opportunity for their own learning, the teachers tell the subject themselves, and there is not enough activity. It can be suggested that the lessons aimed at solving the learning problems experienced by students are taught with games, creating fun learning environments, simplifying the subject, and having more communication between students and teachers.